Cardiac xenografts show reduced survival in the absence of transgenic human thrombomodulin expression in donor pigs. (5th October 2018) - Singh, Avneesh K.; Chan, Joshua L.; DiChiacchio, Laura; Hardy, Naomi L.; Corcoran, Philip C.; Lewis, Billeta G. T.; Thomas, Marvin L.; Burke, Allen P.; Ayares, David; Horvath, Keith A.; Mohiuddin, Muhammad M.
Abstract: A combination of genetic manipulations of donor organs and target‐specific immunosuppression is instrumental in achieving long‐term cardiac xenograft survival. Recently, results from our preclinical pig‐to‐baboon heterotopic cardiac xenotransplantation model suggest that a three‐pronged approach is successful in extending xenograft survival: (a) α‐1, 3‐galactosyl transferase (Gal) gene knockout in donor pigs (GTKO) to prevent Gal‐specific antibody‐mediated rejection; (b) transgenic expression of human complement regulatory proteins (hCRP; hCD46) and human thromboregulatory protein thrombomodulin (hTBM) to avoid complement activation and coagulation dysregulation; and (c) effective induction and maintenance of immunomodulation, particularly through co‐stimulation blockade of CD40‐CD40L pathways with anti‐CD40 (2C10R4) monoclonal antibody (mAb). Using this combination of manipulations, we reported significant improvement in cardiac xenograft survival. In this study, we are reporting the survival of cardiac xenotransplantation recipients (n = 3) receiving xenografts from pigs without the expression of hTBM (GTKO.CD46). We observed that all grafts underwent rejection at an early time point (median 70 days) despite utilization of our previously reported successful immunosuppression regimen and effective control of non‐Gal antibody response. These results support our hypothesis that transgenic expression of human thrombomodulin in donor pigs confers an independent protective effect for xenograft survival in the setting of a co‐stimulation blockade‐based immunomodulatory regimen.